Penguatan Akuntabilitas Keuangan Koperasi melalui Penyusunan PERSUS Kebijakan Akuntansi pada KPUD Kieskendo - Luhgiatno Luhgiatno; Daniel Kartika Adhi; Susanti Wahyuningsih; Panca Wahyuningsih (Fakultas Teknik Universitas Cenderawasih, 2026)
The purpose of this community service activity was to improve the financial accountability of cooperatives by developing a PERSUS on the KPUD Kieskendo in Panunggalan Village, Pulokulon District, Grobogan Regency. The activity was conducted through a workshop and mentoring session involving the cooperative's management and supervisory board. It began with a presentation on the importance of financial accountability, good cooperative governance, and the implementation of SAK EP. The identification results indicated that the cooperative lacked a written accounting policy for internal oversight, financial reporting, and transaction recording. Next, the community service team drafted a PERSUS, which regulates financial reporting, cash and bank management, loan receivables, the formation of CKPN, internal supervision, related party transactions, and fraud prevention. To align the policy with the cooperative's operational needs, discussions on the draft were conducted through participatory, article-by-article discussions. The results of the activity indicated that the management and supervisory board had a better understanding of the benefits of accounting policies for increasing transparency and accountability in cooperative management. It is hoped that the PERSUS will serve as an official guideline for creating more professional, transparent, and sustainable cooperative governance.